Pregunta
upstudy study bank question image url

\( \begin{array}{ll}\text { (4) } \frac{5^{x+4}-5^{x+3}}{100.5^{x+1}} & \text { (5) } \frac{4^{x}+3 \cdot 2^{2 x+1}}{7 \cdot 2^{2 x+1}} \\ \begin{array}{lll}\text { (7) } \frac{8^{x} \cdot 2^{x}+2.16^{x+1}}{11.2^{x+1}} & \text { (8) } \frac{12^{x}+4^{x} \cdot 3^{x+1}}{2^{2 x+4} \cdot 3^{x}} & \text { (6) } \frac{\left(3^{x}\right)^{2}-9^{x-1}}{9^{x-1}} \\ 5.2^{x+1}-7 \cdot 3^{x-1}\end{array} \\ 37\end{array} \)

Ask by Brooks Ortega. in South Africa
Feb 27,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the simplified results for each expression: 1. \( E_4 = 1 \) 2. \( E_5 = \frac{1}{2} \) 3. \( E_6 = 8 \) 4. \( E_7 = 3 \cdot 2^{3x-1} \) 5. \( E_8 = \frac{1}{4} \)

Solución

To solve the given expressions, we will simplify each one step by step. Let's denote the expressions as follows: 1. \( E_4 = \frac{5^{x+4}-5^{x+3}}{100 \cdot 5^{x+1}} \) 2. \( E_5 = \frac{4^{x}+3 \cdot 2^{2x+1}}{7 \cdot 2^{2x+1}} \) 3. \( E_6 = \frac{(3^{x})^{2}-9^{x-1}}{9^{x-1}} \) 4. \( E_7 = \frac{8^{x} \cdot 2^{x}+2 \cdot 16^{x+1}}{11 \cdot 2^{x+1}} \) 5. \( E_8 = \frac{12^{x}+4^{x} \cdot 3^{x+1}}{2^{2x+4} \cdot 3^{x}} \) Let's simplify each expression one by one. ### Simplifying \( E_4 \) \[ E_4 = \frac{5^{x+4} - 5^{x+3}}{100 \cdot 5^{x+1}} \] Factoring out \( 5^{x+3} \) from the numerator: \[ = \frac{5^{x+3}(5 - 1)}{100 \cdot 5^{x+1}} = \frac{4 \cdot 5^{x+3}}{100 \cdot 5^{x+1}} \] Now simplifying: \[ = \frac{4 \cdot 5^{2}}{100} = \frac{100}{100} = 1 \] ### Simplifying \( E_5 \) \[ E_5 = \frac{4^{x} + 3 \cdot 2^{2x+1}}{7 \cdot 2^{2x+1}} \] Rewriting \( 4^{x} \) as \( (2^2)^{x} = 2^{2x} \): \[ = \frac{2^{2x} + 3 \cdot 2^{2x+1}}{7 \cdot 2^{2x+1}} = \frac{2^{2x} + 6 \cdot 2^{2x}}{7 \cdot 2^{2x+1}} \] Factoring out \( 2^{2x} \): \[ = \frac{7 \cdot 2^{2x}}{7 \cdot 2^{2x+1}} = \frac{1}{2} \] ### Simplifying \( E_6 \) \[ E_6 = \frac{(3^{x})^{2} - 9^{x-1}}{9^{x-1}} \] Rewriting \( 9^{x-1} \) as \( (3^2)^{x-1} = 3^{2x-2} \): \[ = \frac{3^{2x} - 3^{2x-2}}{3^{2x-2}} = \frac{3^{2x} - \frac{1}{9} \cdot 3^{2x}}{3^{2x-2}} \] Factoring out \( 3^{2x} \): \[ = \frac{3^{2x}(1 - \frac{1}{9})}{3^{2x-2}} = \frac{3^{2x} \cdot \frac{8}{9}}{3^{2x-2}} = \frac{8 \cdot 3^{2}}{9} = \frac{72}{9} = 8 \] ### Simplifying \( E_7 \) \[ E_7 = \frac{8^{x} \cdot 2^{x} + 2 \cdot 16^{x+1}}{11 \cdot 2^{x+1}} \] Rewriting \( 8^{x} \) and \( 16^{x+1} \): \[ = \frac{(2^3)^{x} \cdot 2^{x} + 2 \cdot (2^4)^{x+1}}{11 \cdot 2^{x+1}} = \frac{2^{4x} + 2 \cdot 2^{4x + 4}}{11 \cdot 2^{x+1}} \] Factoring out \( 2^{4x} \): \[ = \frac{2^{4x}(1 + 2^{5})}{11 \cdot 2^{x+1}} = \frac{2^{4x} \cdot 33}{11 \cdot 2^{x+1}} = \frac{3 \cdot 2^{4x}}{2^{x+1}} = 3 \cdot 2^{3x-1} \] ### Simplifying \( E_8 \) \[ E_8 = \frac{12^{x} + 4^{x} \cdot 3^{x+1}}{2^{2x+4} \cdot 3^{x}} \] Rewriting \( 12^{x} \) and \( 4^{x} \): \[ = \frac{(2^2 \cdot 3)^{x} + (2^2)^{x} \cdot 3^{x+1}}{2^{2x+4} \cdot 3^{x}} = \frac{2^{2x} \cdot 3^{x} + 2^{2x} \cdot 3^{x} \cdot 3}{2^{2x+4} \cdot 3^{x}} \] Factoring out \( 2^{2x} \cdot 3^{x} \): \[ = \frac{2^{2x} \cdot 3^{x}(1 + 3)}{2^{2x+4} \cdot 3^{x}} = \frac{4 \cdot 2^{2x}}{2^{2x+4}} = \frac{4}{16} = \frac{1}{4} \] ### Summary of Results 1. \( E_4 = 1 \) 2. \( E_5 = \frac{1}{2} \) 3. \( E_6 = 8 \) 4. \( E_7 = 3 \cdot 2^{3x-1} \) 5. \( E_8 = \frac{1}{4} \) Now, we can summarize the results or proceed with any further calculations if needed. If you have any

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

Did you know that exponentiation has been used since ancient times, with the Babylonians using base 60 for their number system? They recognized patterns with powers but didn't have a symbol for exponentiation as we do today. Fast forward to the 16th century, and mathematicians like René Descartes started to formalize the rules we follow now. The world of exponents has a rich history that shows the evolution of our understanding of mathematical concepts! When it comes to real-life examples, exponents are all around us! Think of compound interest in finance: when you invest money, the interest earned can also earn interest over time, leading to exponential growth. Similarly, population growth can also be modeled using exponential functions. Understanding these principles can help you navigate both your finances and the world around you!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad